Bimbingan dan Konseling Lintas Budaya Dalam Menjembatani Perbedaan Masyarakat Multikultural - M Fikri Haikal; Abdurrahman Abdurrahman (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Cross-cultural guidance and counseling is an important approach in bridging differences in a multicultural society. Multicultural societies often face challenges in overcoming cultural differences, values ​​and norms that exist among its members. Cross-cultural guidance and counseling aims to help individuals and groups in a multicultural society understand, appreciate, and communicate effectively with people from different cultural backgrounds. In cross-cultural guidance and counseling, there are several approaches and strategies that can be used. First, an educative approach is used to increase understanding of cultural differences and encourage respect for diversity. This is done through the introduction of different cultures, values ​​and norms that exist within them. Second, the therapeutic approach is used to help individuals or groups overcome cultural conflicts and emotional difficulties that may arise from these differences. Cross-cultural guidance and counseling also involves the use of effective communication and problem-solving techniques to help individuals or groups reach an adequate agreement or resolution